Enhanced photocatalytic activity and photocurrent properties of plasma-synthesized indium-doped zinc oxide nanopowder. (March 2019) - Murali, A.; Sarswat, P.K.; Sohn, H.Y.
Abstract: Zinc oxide and indium-doped zinc oxide (IZO) nanopowders (wurtzite crystal phase) were synthesized by plasma-assisted chemical vapor synthesis route. In this method, the injected precursors were vaporized in the plasma flame, followed by vapor-phase reaction and subsequent quenching of the vaporized materials, resulting in the formation of nanoparticles. The amount of indium nitrate was varied to obtain 4 at. % and 8 at. % indium incorporated in zinc oxide, designated as 'IZO1' and 'IZO2', respectively. UV–visible absorbance spectra of the product showed a redshift in the spectra with increasing doping amount of indium. Photocatalytic properties of ZnO and IZO nanoparticles were evaluated using the degradation of methylene blue (MB) under ultraviolet irradiation, and the kinetic analyses indicated that the photodegradation followed pseudo-first order kinetics. In addition, IZO1 nanoparticles exhibited superior photocatalytic activity to ZnO and IZO2 nanoparticles, and the enhancement was attributed to the low recombination rate of photogenerated charge carriers. The major role of defect concentrations (oxygen vacancies) toward MB degradation was also analyzed by Raman and XPS spectra. The effect of scavengers in the photodegradation process indicated that h + and O 2 - were the main oxidant species involved in the degradation process. A mechanism of photodegradation process in IZO was proposed based on Mulliken electronegativity approach. Enhanced photocurrent density was obtained in IZO1, and the electrochemical impedance spectroscopy (EIS) results also pointed to an enhanced separation efficiency of electrons and holes at a lower indium doping amount as in IZO1. Highlights: Zinc oxide and indium-doped zinc oxide nanopowders synthesized by novel plasma-assisted chemical vapor synthesis route. IZO1 (4 at. % In) nanoparticles exhibited superior photocatalytic activity to ZnO and IZO2 (8 at. % In) nanoparticles. Role of defect concentrations (oxygen vacancies) toward methylene blue degradation was analyzed by Raman and X-ray photoelectron spectroscopy spectra. h + and O 2 . - were the main oxidant species involved in the degradation process. Enhanced photocurrent density was observed in IZO1 and electrochemical impedance spectroscopy indicated an enhanced separation efficiency of charge carriers in IZO1.